Castries, St. Lucia. - Le Grand, Joseph (My University, 2018)
Part of the town and military quarters at Morne Fortune. Part of the town and harbour with government house to the left of hill. St. Lucia (Ste Lucie). Postmark on the back dated December 15, 1904. Card addressed to Dr. G. G. Nicholl, Old Bank House,Milford Haven, South Wales, England.
Landscape; black & white , 3 1/2 x 11 in.
Keywords: Aerial views; Aerial photographs; Cities and towns; Landscapes (Representations); Military facilities; Town; Harbour; Morne Fortune